Patellofemoral pain: challenging current practice – a case report - Smith, Benjamin E.; Hendrick, Paul; Logan, Pip (Elsevier, 2016)
Patellofemoral pain (PFP) is a common problem in young people, with 1 in 6 suffering at any one time. It is unclear which management approach is the optimal method for treating PFP in the long term, with traditional physiotherapy examination focusing on assessing for specific structural dysfunction. A rationale for a different assessment and treatment approach, one that moves the focus away from a biomedical/tissue pathology model towards one directed at the neurophysiology of pain, has been suggested.